1998
DOI: 10.1099/0022-1317-79-10-2435
|View full text |Cite
|
Sign up to set email alerts
|

The M1 and NP proteins of influenza A virus form homo- but not heterooligomeric complexes when coexpressed in BHK-21 cells.

Abstract: The nucleoprotein (NP) and matrix protein (M1) are the most abundant structural proteins of influenza A virus. M1 forms a protein layer beneath the viral envelope and NP constitutes the protein backbone of the ribonucleoproteins (RNPs). In order to elucidate the functions of these proteins in virus assembly we have expressed NP and M1 in BHK-21 cells using Semliki Forest virus replicons and analysed their molecular interactions. We found that both M1 and NP engaged in extensive homooligomerization reactions so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 49 publications
0
38
1
Order By: Relevance
“…It has been shown that M1 interacts with vRNP and inhibits transcription (65,70,71). Furthermore, M1 has been shown to bind single-stranded RNA nonspecifically in vitro (12,27) and to bind to vRNP in virus-infected cells (35,50,56) and in virus particles (2,7,58) but not to nucleoprotein (NP) expressed alone (23,74). It was therefore postulated that M1 binds to vRNP via negative charges of the exposed RNA in vRNP.…”
mentioning
confidence: 99%
“…It has been shown that M1 interacts with vRNP and inhibits transcription (65,70,71). Furthermore, M1 has been shown to bind single-stranded RNA nonspecifically in vitro (12,27) and to bind to vRNP in virus-infected cells (35,50,56) and in virus particles (2,7,58) but not to nucleoprotein (NP) expressed alone (23,74). It was therefore postulated that M1 binds to vRNP via negative charges of the exposed RNA in vRNP.…”
mentioning
confidence: 99%
“…In contrast, numerous reports in the literature have documented that the multimerization of matrix (tegument) proteins in structurally less complex RNA viruses play an essential role in virus assembly, particularly in the envelopment (budding) of the particle. As examples, the MAs in vesicular stomatitis virus, the paramyxovirus SV5, Ebola virus, influenza virus, Rous sarcoma virus, and human immunodeficiency virus type 1 (HIV-1) are membrane associated and are proposed to undergo multimerization to create lattice-like structures that have been proposed to lead to the eventual budding or pinching off of that region of the membrane (11,13,15,16,18,20,21,27,33,35,38,39,47,54). Although the recruitment of host cellular functions is necessary for the budding of these viruses, multimerization of their MAs represents an essential viral function in this process (17,19,28,33).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the M1 protein forms homo-oligomers when expressed from a cDNA (54). Moreover, the three-dimensional structure of an amino-terminal fragment of the M1 protein predicts that this protein can form dimers which could self-assemble into large polymers (45).…”
Section: M1 As the Key Element In Influenza Virus Particle Formationmentioning
confidence: 99%
“…COS-1-transfected cultures were harvested and fractionated as described by Zhao et al (54). Briefly, 3 Ï« 10 6 cells were rinsed with phosphate-buffered saline and scraped into 1 ml of a buffer containing 10% (wt/vol) sucrose and 10 mM Tris-HCl (pH 7.5).…”
mentioning
confidence: 99%